Simultaneous Measurement of Neuronal Activity in the Pontine Micturition Center and Cystometry in Freely Moving Mice - Yao, Jiwei; Li, Qianwei; Li, Xianping; Qin, Han; Liang, Shanshan; Liao, Xiang; Chen, Xiaowei; Li, Weibing; Yan, Junan (Frontiers in Neuroscience, 2019)
Understanding the complex neural mechanisms controlling urinary bladder activity is an extremely important topic in both neuroscience and urology. Simultaneously recording of the bladder activity and neural activity in related brain regions will largely advance this field. However, such recording approach has long been restricted to anesthetized animals, whose bladder function and urodynamic properties are largely affected by anesthetics. In our recent report, we found that it is feasible to record bladder pressure (cystometry) and the related cortical neuron activity simultaneously in freely moving mice. Here, we aimed to demonstrate the use of this combined method in freely moving mice for recording the activity of the pontine micturition center (PMC), a more difficultly approachable small region deeply located in the brainstem and a more popularly studied hub for controlling bladder function. Interestingly, we found that the duration of urination events linearly correlated to the time course of neuronal activity in the PMC. We observed that the activities of PMC neurons highly correlated with spike-like increases in bladder pressure, reflecting bladder contractions. We also found that anesthesia evoked prominent changes in the dynamics of the Ca2+ signals in the PMC during the bladder contraction and even induced the dripping overflow incontinence due to suppression of the neural activity in the PMC. In addition, we described in details both the system for cystometry in freely moving mice and the protocols for how to perform this combined method. Therefore, this work provides a powerful approach that enables the simultaneous measurement of neuronal activity of the PMC or any other brain sites and bladder function in freely behaving mice. This approach offers a promising possibility to examine the neural mechanisms underlying neurogenic bladder dysfunction.